A resident boot camp for reducing door-to-needle times at academic medical centers - Ruff, Ilana M. (Neurol Clin Pract, 2017)
BACKGROUND: We sought to determine if a structured educational program for neurology residents can lower door-to-needle (DTN) times at an academic institution. METHODS: A neurology resident educational stroke boot camp was developed and implemented in April 2013. Using a prospective database of 170 consecutive acute ischemic stroke (AIS) patients treated with IV tissue plasminogen activator (tPA) in our emergency department (ED), we evaluated the effect of the intervention on DTN times. We compared DTN times and other process measures preintervention and postintervention. p Values < 0.05 were considered significant. RESULTS: The proportion of AIS patients treated with tPA within 60 minutes of arrival to our ED tripled from 18.1% preintervention to 61.2% postintervention (p < 0.001) with concomitant reduction in DTN time (median 79 minutes vs 58 minutes, p < 0.001). The resident-delegated task (stroke code to tPA) was reduced (75 minutes vs 44 minutes, p < 0.001), while there was no difference in ED-delegated tasks (door to stroke code [7 minutes vs 6 minutes, p = 0.631], door to CT [18 minutes in both groups, p = 0.547]). There was an increase in stroke mimics treated (6.9% vs 18.4%, p = 0.031), which did not lead to an increase in adverse outcomes. CONCLUSIONS: DTN times were reduced after the implementation of a stroke boot camp and were driven primarily by efficient resident stroke code management. Educational programs should be developed for health care providers involved in acute stroke patient care to improve rapid access to IV tPA at academic institutions.